2021
DOI: 10.1111/jcmm.16614
|View full text |Cite
|
Sign up to set email alerts
|

The α2AR/Caveolin‐1/p38MAPK/NF‐κB axis explains dexmedetomidine protection against lung injury following intestinal ischaemia‐reperfusion

Abstract: Intestinal ischaemia‐reperfusion (I/R) injury can result in acute lung injury due to ischaemia and hypoxia. Dexmedetomidine (Dex), a highly selective alpha2‐noradrenergic receptor (α2AR) agonist used in anaesthesia, is reported to regulate inflammation in organs. This study aimed to investigate the role and mechanism of Dex in lung injury caused by intestinal I/R. After establishing a rat model of intestinal I/R, we measured the wet‐to‐dry specific gravity of rat lungs upon treatments with Dex, SB239063 and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Cav-1 participates in a variety of physiological regulations, such as maintaining cell membrane homeostasis, participating in lipid transport, and mediating mitochondrial function. , Lots of receptors for transmembrane factors are present in the caveolae, and Cav-1 can bind directly to the receptors of many signaling molecules to receive external stimuli and conduct transmembrane transduction of signals, resulting in a series of physiological responses in the cell . Cav-1 has been reported to widely exist in the intestine, and it has a regulatory effect on the level of epidermal growth factor (EGF), which plays a vital role in improving the intestinal structure and function of animals and repairing the injured intestine. Further reports indicated that Cav-1 was intimately correlated to oxidative stress and that Cav-1 was likely an oxidative stress-related protein. Cav-1 generally regulates oxidative stress in the same signal pathway as Nrf2 (nuclear erythroid 2 p45-related factor-2) and HO-1 (heme oxygenase-1), which are the most important antioxidant factors in the body and the master switch of the endogenous antioxidant pathway.…”
Section: Introductionsupporting
confidence: 91%
“…Cav-1 participates in a variety of physiological regulations, such as maintaining cell membrane homeostasis, participating in lipid transport, and mediating mitochondrial function. , Lots of receptors for transmembrane factors are present in the caveolae, and Cav-1 can bind directly to the receptors of many signaling molecules to receive external stimuli and conduct transmembrane transduction of signals, resulting in a series of physiological responses in the cell . Cav-1 has been reported to widely exist in the intestine, and it has a regulatory effect on the level of epidermal growth factor (EGF), which plays a vital role in improving the intestinal structure and function of animals and repairing the injured intestine. Further reports indicated that Cav-1 was intimately correlated to oxidative stress and that Cav-1 was likely an oxidative stress-related protein. Cav-1 generally regulates oxidative stress in the same signal pathway as Nrf2 (nuclear erythroid 2 p45-related factor-2) and HO-1 (heme oxygenase-1), which are the most important antioxidant factors in the body and the master switch of the endogenous antioxidant pathway.…”
Section: Introductionsupporting
confidence: 91%
“…Garrean et al [ 22 ] reported that CAV-1 could control the activation of NF-κB, which promotes the inflammation response in ALI. Xu L et al [ 23 ] showed that Dex administration promoted the expression of CAV-1 and suppressed the activation of NF-κB, thus reducing LPS-induced pulmonary injury. However, the precise mechanism by which the CAV-1/NF-κB axis is involved in ALI remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Garrean et al [ 22 ] found that the knockdown of CAV-1 suppresses the activation of NF-κB and inhibits the infiltration of inflammatory cells, to reduce overall mortality. Meanwhile, it has also been reported that the promotion of CAV-1 expression suppresses MAPK and NF-κB activation, alleviating pulmonary inflammation [ 23 ]. However, the exact mechanism by which the CAV-1/NF-κB axis is involved in ALI is still not clear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies ( 22 , 23 ) demonstrated that the α2-AR played a critical role in organ I/R injury. Moreover, suverys found that DEX alleviated intestinal injury ( 9 ) and even remote organ injury ( 10 , 24 ) after intestinal I/R via activating α2-AR, but how it does so remains unclear. In the current study, Yoh, the α2-AR inhibitor, eliminated the intestinal protective effect of DEX, suggesting that DEX protected the intestine against intestinal I/R injury though activating the α2-AR.…”
Section: Discussionmentioning
confidence: 99%
“…The role of DEX in the treatment of intestinal I/R injury has been highlighted in recent studies (5)(6)(7)(8). Moreover, it has been reported that activation of α2-AR by DEX could protect the intestine against intestinal I/R injury (9,10). Nevertheless, the exact mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%